The Use of Journalistic Language in The Headlines of The Waspada Daily Newspaper - Nurhaliza, Siti; Sikumbang, Ahmad Tamrin; Harahap, Suheri (International Journal of Cultural and Social Science, 2023)
The use of good, clear and easy-to-understand language is a benchmark in whether the information conveyed is well received and understandable by the recipient of the information. Journalistic language is a variety of creative language used by the press in writing news in the mass media. Journalistic language has characteristics such as specific, sparing words, not redundant, clear meaning, and communicative. By using concise and clear news language, journalists present interesting information to readers. Journalists often experience problems in applying journalistic language, such as writing under pressure, carelessness and pressing deadlines. In this study the authors focus on the main news or the main page. The main story is also referred to as the intro, meaning that the section is intended to make it easier for the reader to find out the contents of the news quickly. This study aims to determine the use of the language of the Daily Waspada newspaper. This study uses a qualitative approach, and the type of research is descriptive content analysis. The descriptive type of content analysis is used by researchers to provide an overview of the use of journalistic language analysis funds in the Waspada Daily newspaper. In collecting the data, the researcher conducted interviews and directly examined the news text in the main news of the Waspada Daily newspaper. The results of the research are that researchers in using the language of Harian Waspada apply journalistic language that is guided by the Big Indonesian Dictionary and Enhanced Spelling. Apart from that, the Waspada Daily also continues to rely on KBBI and guidebooks for news writing or procedural operational standards (SOPs). Then from the 5 headlines analyzed, the characteristics are not redundant and sparing words that are often violated.